Organic reactions - Evans, P. Andrew; Kazmaier ,Uli; Ullrich ,Angelika (Hoboken : Wiley, 2023)
"Organic chemistry is all about making complex molecules from simple precursors by way of a chemical reaction. Understanding and controlling chemical reactions is a core skill for all chemists, whether they are working in industry or in academia"--
Includes index.
Keywords: Organic Reactions